Gross and Histopathological Dermal Changes at Sites of Snakebite – Report from Autopsy Series - Ghosh, Soma; Mondal, Soumya Kanti; Hembram, Partha Sarathi (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Snake bite remains a significant cause of accidental death, its occurrence usually underestimated because of under reporting. Objective: To report on gross and microscopic changes at sites of snakebite in autopsy. Methods: A cross-sectional, descriptive study was conducted on thirty cadavers of snake bite for study duration of one year based on inclusion and exclusion criteria. Skin was collected from sites of bite. Gross examination was carried out on formalin fixed specimens. Microscopic examination was performed on dermal biopsy of formalin fixed paraffin embedded sections stained with haematoxylene and eosin (H&E). Results: 53.4% of deceased were in the age group of 41-50 years. Males were predominant in the study (90%) where 63.3% were agriculture workers. Lower limb bite was commonly seen (83.3%) in outdoor locales (90%). Snakes identified were cobra and viper. Death occurred within 48 hours of admission in 80% cases. Bite mark was visualised in ten cases and ulceration in three. Microscopic examination revealed normal epidermis in 53.3% cases. Abnormalities seen included acantholysis in 36.7% and ulceration in 10%cases. Dermal changes were coagulative necrosis (26.7%), fibrinoid necrosis (16.7%), haemorrhagic necrosis (20%), oedema (13.3%). Combination of changes in a particular case also observed. Vascular changes comprised of extravasation (30%), fibrinoid necrosis with microvascular damage (23.4%), vasculitis (13.3%), microvascular damage (26.7%). Perineural fibrosis, subcutaneous gangrenous and haemorrhagic fat necrosis were other observations. Conclusion: This study highlights histological profile of dermal changes by snake venom at site of bite that can enlighten its pathophysiologic effects on cutaneous tissue. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 132-139